209k views
2 votes
Simplify the expression (2t-8)-1/2(9-4t)+5/2

User Marienke
by
6.7k points

1 Answer

5 votes
= (2t - 8) - 1/2(9 - 4t) + 5/2
multiply 1/2 by parentheses

= (2t - 8) + (-1/2 * 9) + (-1/2 * - 4t) + 5/2
multiply in parentheses

= 2t - 8 - 9/2 + 4/2t + 5/2
combine like terms

= 2t - 8 - 9/2 + 2t + 5/2
divide 4/2 into 2 and add to 2t

= 4t - 8 - 9/2 + 5/2
combine fractions

= 4t - 8 - 4/2
divide 4/2 into 2

= 4t - 8 - 2

= 4t - 10


ANSWER: 4t - 10

Hope this helps! :)
User Bruno Casali
by
6.8k points